Making foreign policy presidential management of the decision-making process - Mitchell, David 1972- (Ashgate, 2005)
"This influential study presents an advisory system theory of decision-making to examine cases of presidential policy formulation drawn from the Nixon, Carter, Reagan, Clinton and Bush administrations. Easily accessible to scholars, graduates and advanced undergraduates interested in US foreign policy or foreign policy analysis, presidential studies, and bureaucracy and public administrations scholars, and to practitioners and those with a general interest in International Relations."--Jacket.